2009
DOI: 10.1289/ehp.0901015
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Organohalogens, Including Brominated Flame Retardants, Influences Motor, Cognitive, and Behavioral Performance at School Age

Abstract: BackgroundOrganohalogen compounds (OHCs) are known to have neurotoxic effects on the developing brain.ObjectiveWe investigated the influence of prenatal exposure to OHCs, including brominated flame retardants, on motor, cognitive, and behavioral outcome in healthy children of school age.MethodsThis study was part of the prospective Groningen infant COMPARE (Comparison of Exposure-Effect Pathways to Improve the Assessment of Human Health Risks of Complex Environmental Mixtures of Organohalogens) study. It inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
216
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(227 citation statements)
references
References 35 publications
8
216
3
Order By: Relevance
“…Cowpea and fish samples have the highest number of alkane in all the market sampled, although studies have investigated alkane in the environment [18;19], dust [20], human serum [21], human milk [22], and animal tissues [23,24], few have examined alkane contamination of food. Toxicity studies suggest that the alkane is an endocrine disruptor and developmental neurotoxicant; specifically, some alkane compound have been associated with changes in rat thyroid systems [25,26], altered function of human natural killer cells [27;28], and neurotoxic effects such as decreased fine manipulative abilities and lower attention in children [29].…”
Section: Discussionmentioning
confidence: 99%
“…Cowpea and fish samples have the highest number of alkane in all the market sampled, although studies have investigated alkane in the environment [18;19], dust [20], human serum [21], human milk [22], and animal tissues [23,24], few have examined alkane contamination of food. Toxicity studies suggest that the alkane is an endocrine disruptor and developmental neurotoxicant; specifically, some alkane compound have been associated with changes in rat thyroid systems [25,26], altered function of human natural killer cells [27;28], and neurotoxic effects such as decreased fine manipulative abilities and lower attention in children [29].…”
Section: Discussionmentioning
confidence: 99%
“…Then 5 ng of each internal standard ( 13 C 12 -labeled BDE28, BDE47, BDE99, BDE153, BDE154, and BDE183) was added to the samples. 13 C 12 -labeled BDE139 was added as the recovery spike. The quantification of PBDEs was performed using a GC (Agilent 7890A) equipped with a mass-selective detector (Agilent 5975C) using the electron impact (EI) mode.…”
Section: Reagentsmentioning
confidence: 99%
“…Recently, there is increasing evidence that PBDEs have corresponding adverse effects on human health. For example, based a study combined children's development with pollutant burdens in their mothers, Roze et al (2009) concluded that transplacental transfer of PBDEs were associated with the neurodevelopment of children at school age. Turyk et al (2008) found that increased thyroglobulin antibodies and increased T4 in adult males were associated with PBDE exposure.…”
Section: Potential Health Risk Of High Burdens Of Pcbs and Pbdes For mentioning
confidence: 99%